The role of information technology in solving the problems of administrative sports federations An exploratory study of the opinions of a number of managers of sports federations in Kirkuk Governorate - إبراهيم رجب العكدي, سوسن; فاضل محسن, اياد; اكرم ارسلان, مؤيد (Journal of College of Education, 2020)
This research aims to show the extent of the role of information technology in solving the problems of administrative sports federations. It seeks to demonstrate the extent to which the information technology adopted by the sports associations in Kirkuk governorate can solve administrative problems that can be faced in its daily work. In order to achieve this, a questionnaire was used for this purpose, distributed exclusively to the heads of the sports federations or their representatives in the governorate of Kirkuk, and the number of (28) individuals, and all the answers within the questionnaire were processed depending on a set of statistical tests appropriate and consistent with the objective of the study, Which enabled us to reach a set of conclusions on which we built a set of recommendations that we hope will be useful for the research organizations, as well as other organizations within the sports sector.